Social Capital, Knowledge Sharing and MSMEs Performance: The Mediating Role of Entrepreneurial Competence - Widiyanto Widiyanto; Ahmad Nurkhin; Minkhatul Fikriyah (Universitas Negeri Malang, 2022)
This study is intended to explain the mediating role of entrepreneurial competence in determining the effect of social capital and knowledge sharing on the performance of convection micro, small and medium-sized enterprises (MSMEs) in the Pemalang Regency in Indonesia. Researchers used this type of causality research to analyze the relationship between variables. The participants in the study are the owners of MSMEs Convection in Samong Village, Ulujami District, Pemalang Regency. This study obtained 285 sample units using a simple random sampling technique. Questionnaires were used to collect research data. The data analysis method used is path analysis. The results of this study indicate that social capital, knowledge sharing, and entrepreneurial competence can all significantly affect MSMEs performance. Entrepreneurial competence has a more dominant effect on MSMEs performance. In addition, social capital and knowledge sharing can both have a significant effect on entrepreneurial competence. The mediating role of entrepreneurial competence is evident in the effect of social capital and knowledge sharing on MSMEs performance. Social capital and knowledge sharing can improve MSMEs performance if owners have adequate entrepreneurial competence. Therefore, owners should maintain social capital and manage their knowledge. Keywords: MSMEs performance, social capital, knowledge sharing, entrepreneurial competence